2018
DOI: 10.1103/physrevd.98.084019
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect fluid description of modified gravities

Abstract: The Brans-Dicke-like field of scalar-tensor gravity can be described as an imperfect fluid in an approach in which the field equations are regarded as effective Einstein equations. After completing this approach we recover, as a special case, the known effective fluid for a scalar coupled nonminimally to the Ricci curvature and we describe the imperfect fluid equivalent of f (R) gravity. A symmetry of electrovacuum Brans-Dicke gravity is translated into a symmetry of the corresponding effective fluid. The disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 132 publications
(120 reference statements)
3
74
0
Order By: Relevance
“…Depending on the characteristics of the detected expansion anisotropy, it could be illuminating to the nature of inflaton, dark energy (DE) and even gravitation. For instance, altering the stiff-fluid-like behavior of the expansion anisotropy could be possible mainly by either replacing minimally coupled scalar field models of inflaton or DE by a source yielding anisotropic pressure (e.g., vector fields; see [12] for a list of anisotropic stresses and their effects on the expansion anisotropy) or replacing GR by a modified gravity that can give rise to effective source yielding anisotropic pressure (e.g., Brans-Dicke theory [13][14][15]); see, for examples, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the characteristics of the detected expansion anisotropy, it could be illuminating to the nature of inflaton, dark energy (DE) and even gravitation. For instance, altering the stiff-fluid-like behavior of the expansion anisotropy could be possible mainly by either replacing minimally coupled scalar field models of inflaton or DE by a source yielding anisotropic pressure (e.g., vector fields; see [12] for a list of anisotropic stresses and their effects on the expansion anisotropy) or replacing GR by a modified gravity that can give rise to effective source yielding anisotropic pressure (e.g., Brans-Dicke theory [13][14][15]); see, for examples, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Within this approach, the correspondence between general scalar-tensor theories and this effective fluid has been worked out explicitly first in [111] (see also [112] for the preceding work), and has shown that, in general, the corresponding effective fluid is imperfect. A recent work [113] extended and completed the correspondence showing how a symmetry of BD theory translates into a symmetry of this fluid such that this correspondence is valid for any spacetime geometries. Brans and Dicke's 1961 theory [106,110], motivated first by the implementation of Mach's principle in gravity, today provides a prototype of scalar-tensor theories [107][108][109].…”
Section: Introductionmentioning
confidence: 90%
“…The entropy perturbation, e.g., is one of the two basic dynamical quantities in our context and neither velocity components nor metric functions do appear explicitly in the system of equations. An imperfect fluid description of scalar-tensor theories has been recently performed also in [21].…”
Section: E Perturbations Of (An-)isotropic Pressures and Energy Fluxmentioning
confidence: 99%
“…In the presence of an adequate timelike vector field, this energymomentum tensor is then characterized by an energy density, a scalar isotropic pressure, an anisotropic pressure and an energy flux. It has the structure of the energy-momentum tensor of an imperfect fluid [18][19][20][21]. Imperfect-fluid dynamics can provide an effective description for cosmological models beyond the standard model.…”
Section: Introductionmentioning
confidence: 99%